Development of Mobile Internet and Its Effect on IPv6 - Shengkai Wang; Ning Kong; Shuo Shen (Dianxin kexue)
The development of application and technology of international and domestic mobile internet were described, the mutual effect and relationship between mobile internet and IPv6 were analyzed, and the future of mobile internet and IPv6 were discoussed. In the end, from the views of technology, application and governance, some measures and recommendations on how to promote the development of mobile internet and IPv6 in the future were proposed.